REVISION OF THE GENUS CATANTHERA F.v. MUELL. (MELASTOMATACEAE) - M. P. Nayar (REINWARDTIA, 1982)
A historical sketch of the genus Catantlicra is presented and its relationship with the two allied genera Dissockaeta Bl. and Mediniltu Gaud, is discussed. The 16 species recognised in the genus Cntantkcra are described and a key to the species so far known is presented. The genus Cata-nthera is entirely restricted to Malesia, occuring in New Guinea, Borneo and Sumatra. They are ivy-like climbers which form a canopy in the tropical rain forests. Five new species, Catanthera royenii Nayar, C. pifosa Nayar, C. novoguinevnsis Nayar, C. Hleuineri Nayar and C. peltata Nayar are described and illustrated.